A posteriori error estimate for discontinuous Galerkin finite element method on polytopal mesh. Issue 3 (21st November 2019) - Cui, Jintao; Gao, Fuzheng; Sun, Zhengjia; Zhu, Peng
Abstract: In this work, we derive a posteriori error estimates for discontinuous Galerkin finite element method on polytopal mesh. We construct a reliable and efficient a posteriori error estimator on general polygonal or polyhedral meshes. An adaptive algorithm based on the error estimator and DG method is proposed to solve a variety of test problems. Numerical experiments are performed to illustrate the effectiveness of the algorithm.